Anal cancer screening and prevention: a review for dermatologists. (11th June 2021) - McGovern, J.; Fuller, C.; Burris, K.
Abstract: The incidence of and mortality from anal cancer, predominantly squamous cell carcinoma (SCC), have been increasing since the 1980s, during an era when many common malignancies have seen decreases in mortality. Dermatologists may be more likely to see patients at an increased risk for anal SCC, such as those living with HIV, MSM and those presenting for management of anogenital warts, yet there is little guidance in the field on how to manage these patients. We underwent a project to review the evidence surrounding screening and prevention of anal SCC. HPV vaccination, the main preventative measure for anal SCC, is often underutilized and may not be effective for those most at risk. Screening methods currently include high‐risk HPV and anal cytology testing, with high‐resolution anoscopy (HRA) reserved for biopsy and confirmatory testing. High‐risk HPV testing has been associated with high sensitivity for intraepithelial neoplasia, but low specificity in high‐risk groups. Recent meta‐analyses examining AIN detection using anal cytology estimate a similarly high sensitivity of 74–87%, with a relatively higher specificity (44–66%) for identifying high‐grade AIN. HRA is the gold standard for diagnosis, but its accessibility and cost are deterrents from its use as a screening tool. Cervical cancer screening, initially adopted without significant evidence of its impact, has significantly decreased cervical cancer rates. The argument can be made that rates of anal SCC may also benefit from appropriate screening methods, particularly anal cytology. It is prudent for dermatologists to be aware of the methods available to them in the management of at‐risk patients, the data supporting them, and the potential benefits of screening in order to counsel patients appropriately and address the increasing burden of disease.